Radiocarbon Dating of an Olive Tree Cross-Section: New Insights on Growth Patterns and Implications for Age Estimation of Olive Trees - Ehrlich, Yael; Regev, Lior; Kerem, Zohar; Boaretto, Elisabetta (Frontiers in Plant Science, 2017)
The age of living massive olive trees is often assumed to be between hundreds and even thousands of years. These estimations are usually based on the girth of the trunk and an extrapolation based on a theoretical annual growth rate. It is difficult to objectively verify these claims, as a monumental tree may not be cut down for analysis of its cross-section. In addition, the inner and oldest part of the trunk in olive trees usually rots, precluding the possibility of carting out radiocarbon analysis of material from the first years of life of the tree. In this work we present a cross-section of an olive tree, previously estimated to be hundreds of years old, which was cut down post-mortem in 2013. The cross-section was radiocarbon dated at numerous points following the natural growth pattern, which was made possible to observe by viewing the entire cross-section. Annual growth rate values were calculated and compared between different radii. The cross-section also revealed a nearly independent segment of growth, which would clearly offset any estimations based solely on girth calculations. Multiple piths were identified, indicating the beginning of branching within the trunk. Different radii were found to have comparable growth rates, resulting in similar estimates dating the piths to the 19th century. The estimated age of the piths represent a terminus ante quem for the age of the tree, as these are piths of separate branches. However, the tree is likely not many years older than the dated piths, and certainly not centuries older. The oldest radiocarbon-datable material in this cross-section was less than 200 years old, which is in agreement with most other radiocarbon dates of internal wood from living olive trees, rarely older than 300 years.